Smouldering Fires and Natural Fuels - Rein,G (2013)
This chapter argues that smouldering combustion leads to megafires as measured in terms of the total organic material consumed. The chapter reviews the current knowledge on smouldering fires in the Earth system regarding combustion dynamics and chemistry, while highlighting differences with flaming fires. It shows that smouldering combustion of natural ground fuels, like peatlands, leads to the largest and longest burning fires on Earth, and shows that they create a positive feedback mechanism to climate change. It is therefore absolutely crucial for us to expand our limited knowledge of not only flaming, but also particularly of smouldering fires. Flaming wildfires have received much more attention than smouldering fires hitherto; this chapter aims at reversing that trend and contributing new forward-looking ideas to the important study of flameless fires. © 2013 John Wiley & Sons, Ltd.